The Oxytocin–Bone Axis. (February 2014) - Colaianni, G.; Tamma, R.; Di Benedetto, A.; Yuen, T.; Sun, L.; Zaidi, M.; Zallone, A.
<x xml:space="preserve">Abstract</x> We recently demonstrated a direct action of oxytocin (OT) on skeletal homeostasis, mainly mediated through stimulation of osteoblasts (OBs) formation and through the reciprocal modulation of osteoclast (OCs) formation and function. Thus, mice lacking the hormone or its receptor develop a low turnover osteoporosis that worsens with age in both sexes. The skeletons of OT (Ot) and OT receptor (Oxtr) null mice display a pronounced decrease in vertebral and femoral trabecular volume. At the cellular level, OBs from Ot KO and Oxtr KO mice exhibit lower mineralization activity and, at the mRNA level, all master genes for osteoblast differentiation are down‐regulated. Moreover, OT has dual effects on OCs: it increases osteoclast formation both directly, by activating nuclear factor kB (NFkB) and mitogen‐activated protein kinase (MAPK) signalling and, indirectly, through the up‐regulation of receptor activator nuclear factor‐kappaB ligand synthesis by OBs. On the other hand, it inhibits bone resorption by triggering cytosolic Ca2+ release and nitric oxide synthesis in mature OCs. OT is locally produced by osteoblasts acting as paracrine‐autocrine regulators of bone formation modulated by oestrogens. The oestrogen signal involved in this feedforward circuit is nongenomic because it requires an intact MAPK kinase signal transduction pathway, instead of the classical nuclear translocation of oestrogen receptor. The ability of oestrogen to increase bone mass in vivo is to some extent OXTR‐dependent. Thus, Oxtr KO mice injected 17β‐oestradiol did not show any effects on bone formation parameters, whereas the same treatment increases trabecular and cortical bone in wild‐type mice. An intact OT autocrine‐paracrine circuit appears to be essential for optimal skeletal remodelling.